Lebanon : Assessment of the Public Procurement System - World Bank (World Bank, Washington, DC, 2021)
Public procurement is one of the main cross-sectoral reforms that the Government of Lebanon committed to at the “Conférence économique pour le développement, par les réformes et avec les entreprises” (CEDRE) held in Paris in April 2018, in order to improve fiscal governance and the quality of public services, encourage investment inflows, and strengthen accountability and transparency. Public procurement accounts for an average of 20% of central government expenditure and 6.5% of the Gross Domestic Product (thus, around USD 3.4 billion in 2019) at the central level. A coherent and clear public procurement system in line with international standards and based on sound legal and institutional foundations is thought to improve competitiveness of the economy, attract quality service providers, strengthen accountability and transparency and achieve savings on yearly basis, allowing for more fiscal space to finance public investments and for enhancing service delivery to citizens. As a result, it would considerably contribute to helping resolve the current economic and financial crisis and create the basis for the implementation of the Government’s vision for economic recovery and sustainable development.